123k views
0 votes
Fit a quadratic function to these three points (-1, -11) (0,-3) and (3,-27)

User Auco
by
5.6k points

1 Answer

2 votes

ANSWER


y = - 4 {x}^(2) + 4x - 3

Step-by-step explanation

Let the quadratic function be


y = a {x}^(2) + bx + c

We substitute each point to find the constants, a,b, and c.

Substitute: (x=0,y=-3)


- 3 = a {(0)}^(2) + b(0) + c


\implies \: c = - 3...(1)

Substitute: (x=-1,y=-11) and c=-3


- 11 = a {( - 1)}^(2) + b( - 1) + - 3


\implies \: - 11 = a - b - 3


\implies \: a - b = - 8...(2)

Substitute: (x=3,y=-27) and c=-3


-27= a {( 3)}^(2) + b( 3) + - 3


\implies \: - 27 = 9a + 3b - 3


\implies \: 3a + b = - 8...(3)

Add equations (3) and (2)


3a + a = - 8 + - 8


4a = - 16


a = - 4

Put a=-4 in equation (2)


- 4 - b = - 8


- b = - 8 + 4


- b = - 4


b = 4

The quadratic equation is


y = - 4 {x}^(2) + 4x - 3

User Dennis Van Gils
by
5.0k points